Data supporting: 'The importance of non-stationary multiannual periodicities in the North Atlantic Oscillation index for forecasting water resource drought' - Rust, William; Holman, Ian P.; Bloomfield, John P.; Cuthbert, Mark (Cranfield University, 2022)
1- 157 x 136 matrix containing calculated drought series for each 136 GWL records over 157 years. NAs present where no GWL record present. Drought threshold method used after Peters et al, 2003.2 - 139 x 767 matrix containing calculated streamflow drought series for 767 streamflow gauges over 139 years. Value represents Boolean of whether a drought occurred in calendar year.3 - 201 x 157 x 136 array of cross-wavelet transform pval results between 136 groundwater level records over 157 years at 201 frequency intervals. NA values present where no values recorded in original GWL series.4 - 201 x 157 x 767 array of cross-wavelet transform pval results between 767 streamflow records over 157 years at 201 frequency intervals. NA values present where no values recorded in original GWL series.5 - 201 x 157 x 136 array of cross-wavelet transform power results between 136 groundwater level records over 157 years at 201 frequency intervals. NA values present where no values recorded in original GWL series.6 - 5 - 201 x 157 x 767 array of cross-wavelet transform power results between 767 streamflow records over 157 years at 201 frequency intervals. NA values present where no values recorded in original GWL series.7 - 157 x 136 matrix containing phase difference values between the NAO and 136 groundwater level records over 157 year time period. Phase difference for the 7.5 year periodicity.8 - 157 x 767 matrix containing phase difference values between the NAO and 767 streamflow records over 157 year time period. Phase difference for the 7.5 year periodicity.
Keywords: Surfacewater Hydrology'; 'Water Resources Engineering'